Explore The Technique of Peripheral Anesthesia and Its Relationship with Ultrasound Utilization from the Perspectives of Physicians and Anesthesiologists - Faraj Khamees Saqar; Badr Al-Din Mohammed Jumaa; Wafa Mohamed Masud; Jumaa Mohamed Salh (المجلة الأفروآسيوية للبحث العلمي, 2024)
The article discusses peripheral anesthesia, also known as regional anesthesia, which specifically targets nerves to numb particular areas of the body. The study aimed to explore the technique of peripheral anesthesia and its association with ultrasound use from the perspectives of doctors and anesthesiologists. A total of 34 participants were involved in the study, with data collected from medical professionals in various settings, including private and public clinics and hospitals, through a specially designed questionnaire. Results indicated that 41.2% of participants specialized in human medicine, while 38.2% had 5 to 10 years of experience. Potential contraindications for peripheral anesthesia, such as brain tumors, infections, or significant blood loss, were identified with a mean score of 2.26 and a standard deviation of 0.89. The study also found that peripheral anesthesia is perceived as risk-free for patients, with a mean score of 2.17 and a standard deviation of 0.83. A strong positive correlation (0.42, p = 0.007) was noted between the perceptions that peripheral anesthesia does not cause side effects post-operation and that it poses no risks to patients. The study concluded that while peripheral anesthesia is one of the safest anesthesia methods, its application remains limited due to the novelty of the specialty and the complexity of the procedures. The authors recommended increasing attention to peripheral anesthesia to help mitigate the risks associated with general anesthesia and to fully leverage its benefits.